2017
DOI: 10.18632/oncotarget.17504
|View full text |Cite
|
Sign up to set email alerts
|

The novel complex combination of alum, CpG ODN and HH2 as adjuvant in cancer vaccine effectively suppresses tumor growth in vivo

Abstract: Single-component adjuvant is prone to eliciting a specific type of Th1 or Th2 response. So, the development of combinatorial adjuvants inducing a robust mixed Th1/Th2 response is a promising vaccination strategy against cancer. Here, we describe a novel combination of aluminum salts (alum), CpG oligodeoxynucleotide (CpG) and innate defense regulator peptide HH2 for improving anti-tumor immune responses. The CpG-HH2 complex significantly enhanced the production of IFN-γ, TNF-α and IL-1β, promoted the uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Confirmed by flow cytometric phenotyping, a mixture of highly activated, efficiently target cell killing NK cells and cytotoxic T cells attack MLH1 ¡/¡ tumor targets; the latter in an MHC-I restricted manner. 32,33 Another interesting finding of this study was the increased mutational load in selected MSI-target genes from vaccinated tumors, which likely constitutes some kind of escape mechanism by triggering antigenic drift. Together with the missing activation of T helper cells and upregulation of immune-checkpoint molecules this best explains final disease progression and treatment failure.…”
Section: E1408748-8mentioning
confidence: 83%
“…Confirmed by flow cytometric phenotyping, a mixture of highly activated, efficiently target cell killing NK cells and cytotoxic T cells attack MLH1 ¡/¡ tumor targets; the latter in an MHC-I restricted manner. 32,33 Another interesting finding of this study was the increased mutational load in selected MSI-target genes from vaccinated tumors, which likely constitutes some kind of escape mechanism by triggering antigenic drift. Together with the missing activation of T helper cells and upregulation of immune-checkpoint molecules this best explains final disease progression and treatment failure.…”
Section: E1408748-8mentioning
confidence: 83%
“…These results suggest that NACH vaccine can significantly induce humoral immunity against multiple myeloma. Tian et al's 31 findings also suggest that vaccine combined with Alum-CpG-HH2 combinational adjuvant significantly increases the concentration of IgG in the blood of mice.…”
Section: Discussionmentioning
confidence: 94%
“…29,30,32 A previous study indicated that alum-CpG ODN-HH2 complex was an effective and novel immune adjuvant. 31 In our current study, we develop a complex vaccine based on NY-ESO-1-alum-CpG ODN-HH2 (named NACH) and examine its anti-tumor effects and immunogenicity on prophylactic and therapeutic models of murine multiple myeloma. We found that alum, CpG ODN, and HH2 complex as novel immune adjuvant combined cancer vaccine could improved the immunity efficient in murine multiple myeloma model.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide nanoparticles can also be used as potent carriers for vaccine delivery and can be used as antitumor agents for cancer therapy. A very recent study described a superparamagnetic Fe 3 O 4 as a delivery system of OVA, showing superior induction of both immune cell activation and cytokine production with effective control of tumor growth [59]. Indeed, magnetic nanoparticles can be directly controlled by an external magnetic field to significantly improve lymph node as well as intra-tumor retention [60].…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%